Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/pi.6273
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte complexes of chitosan and sodium alginate as a drug delivery system for diclofenac sodium

Abstract: Polyelectrolyte complexes (PECs) have unique physicochemical properties which make them very interesting for pharmaceutical applications and particularly as drug delivery systems. The aim of this work was to obtain PECs based on the biocompatible and biodegradable biopolymers chitosan and sodium alginate and to apply them as a drug delivery system for sustained release of diclofenac sodium. Three complexes with different ratios between the two polyions were obtained. Their structure and properties were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This anomalous (or non-Fickian) mechanism is known in the literature as pseudo-Fickian diffusion, indicating that in the first step of drug release this process is limited by swelling [ 38 ]. It is consistent with the results obtained by Nikolova et al, who observed n values greater than 0.45 for the release of diclofenac sodium from CS/ALG hydrogels composed of 0.05% ( w/w ) CS and 0.05% ( w/w ) ALG solutions in ratio 1:2 [ 39 ].…”
Section: Resultssupporting
confidence: 92%
“…This anomalous (or non-Fickian) mechanism is known in the literature as pseudo-Fickian diffusion, indicating that in the first step of drug release this process is limited by swelling [ 38 ]. It is consistent with the results obtained by Nikolova et al, who observed n values greater than 0.45 for the release of diclofenac sodium from CS/ALG hydrogels composed of 0.05% ( w/w ) CS and 0.05% ( w/w ) ALG solutions in ratio 1:2 [ 39 ].…”
Section: Resultssupporting
confidence: 92%
“…The observed trends are understandable considering the acid-base properties of collagen and chitosan. Researchers have documented that chitosan displays typical polyelectrolytic properties that underlie its ability to form complexes with other molecules, such as pharmaceuticals [64] and biopolymers [65,66]. This specific feature of chitosan is associated with the presence of protonated amino groups (pKa ≈ 6.3 [67]), which enables it to interact with negatively charged species.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the maximum loading for LHCl was surprisingly only 50% for gels having a similar swellability. The difference in the loading capacity is therefore likely attributed to electrostatic interactions between the drug and the polymer chains . While DS is in its neutral (COOH) form in acidic conditions, LCHL remains positively charged and hence exhibits electrostatic repulsion with the polymer backbone.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The difference in the loading capacity is therefore likely attributed to electrostatic interactions between the drug and the polymer chains. 43 While DS is in its neutral (COOH) form in acidic conditions, LCHL remains positively charged and hence exhibits electrostatic repulsion with the polymer backbone. This becomes particularly apparent in samples S4 and S5 (loading capacity of <20%), as these polymers contain the highest content of positively charged APTAC and are therefore the most electrostatically repulsive.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%